Cancer incidence of larger thyroid nodules and the diagnostic value of palpation and ultrasound guided fine needle aspiration biopsy - Umut Rıza Gündüz; Arif Aslaner; Rojbin Karakoyun Demirci; Hasan Çalış; Osman Zekai Öner; Nurullah Bülbüller (American Journal of Experimental and Clinical Research, 2014)
In this prospective study, we aimed to determine the cancer incidence of thyroid nodules larger than 3cm and compare the efficacy of palpation and ultrasound guided fine needle aspiration biopsy (FNAB). The study was conducted at General Surgery Departments of Istanbul Okmeydanı and Antalya Training and Research Hospitals of Turkey from March 2008 to December 2011. In our clinics, between the years 2008 and 2011, both palpation and ultrasound guided FNAB were performed in all 55 patients having thyroid nodules larger than 3 cm. The results were determined as inadequate, benign, suspicious and malignant. Histopathological findings were compared with the results of both palpation and ultrasound guided FNAB and sensitivity, specificity and accuracy rates were calculated. The specificity (98%) and accuracy rate (92.72%) of ultrasound guided FNAB corresponded to those from the literature, except the rate of sensitivity (40%). This is explained by FNAB performed only on the dominant nodule. Ultrasound guided FNAB is an efficient and reliable diagnostic method when performed by experienced clinicians. Hematoma and pain are such rare complications. Ultrasound plays an important role in taking biopsy from the true solid thyroid nodules. We conclude that ultrasound guided FNAB is the gold standard method in the diagnosis of thyroid nodules.